Safety profiles of sevoflurane in pediatric patients: a real-world pharmacovigilance assessment based on the FAERS database - Yang, Chuang; Deng, Bangjian; Wen, Qiang; Guo, Pei; Liu, Xiang; Wang, Chen (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the safety profile of sevoflurane in pediatric populations using real-world data.MethodsData were extracted from the Food and Drug Administration Adverse Event Reporting System (FAERS) from the first quarter of 2004 to the third quarter of 2024. We analyzed reports where sevoflurane was the primary suspect in individuals aged 0–18, employing disproportionality analysis to detect adverse events associated with sevoflurane. We also compared the adverse events related to sevoflurane between pediatric and adult populations.ResultsThe FAERS database yielded 21,838,627 adverse event reports for children, with 474 involving sevoflurane as the primary suspect. Descriptive analysis revealed a majority of reports from male patients, primarily reported by physicians. Disproportionality analysis identified significant System Organ Classes (SOC) signals associated with sevoflurane, meeting four detection criteria, including “Cardiac disorders,” “Respiratory, thoracic, and mediastinal disorders,” and “Vascular disorders.” The study also identified previously unreported adverse events, such as “Encephalopathy” and “Hypercapnia.” Notable differences in signals were observed between children and adults for “Pulmonary alveolar hemorrhage,” “Anaphylactic shock,” and “Hypotension.”ConclusionOur analysis of the FAERS database identified several significant adverse events associated with sevoflurane in pediatrics, affecting the cardiovascular, respiratory, and nervous systems. Differences in adverse event signals between children and adults were also observed. Furthermore, the new adverse events (such as encephalopathy and hypercapnia) indicated that anesthesiologists should be more vigilant in administering sevoflurane.